ASSESSMENT OF GAIT AND POSTURAL BALANCE OF CHILDREN AND PRE-ADOLESCENTS WITH ACQUIRED AND CONGENITAL VISUAL IMPAIRMENT: A CROSS-SECTIONAL STUDY (CIPEEX, 2022)
THE AIM OF THE STUDY IS TO CHARACTERIZE THE GAIT PATTERN, MOTOR CONTROL AND POSTURAL BALANCE OF CHILDREN AND PRE-ADOLESCENTS WITH ACQUIRED AND CONGENITAL VISUAL IMPAIRMENT. THIS IS A CROSS-SECTIONAL STUDY WITH A CONVENIENCE SAMPLE OF 10 CHILDREN AND PRE-ADOLESCENTS WITH ACQUIRED AND CONGENITAL VISUAL IMPAIRMENT AGED BETWEEN 6 AND 12 YEARS AND 10 CHILDREN AND PRE-ADOLESCENTS WHO ARE SIGHTED IN THE SAME AGE GROUP PERFORMING THE FOLLOWING ASSESSMENTS: OF BALANCE THROUGH THE PEDIATRIC BALANCE SCALE, SPATIOTEMPORAL PARAMETERS OF GAIT, CONTROL OF STATIC AND DYNAMIC BALANCE, FUNCTIONAL MOBILITY THROUGH TIMED UP GO. THE RESULTS FROM THIS STUDY WILL BE DISSEMINATED WITH EXCELLENCE IN THE SCIENTIFIC ENVIRONMENT, PROVIDING GROWTH AND CONTINUITY IN CORRELATED RESEARCH. ONE OF THE MAIN EXPECTATIONS OF THE IMPACT OF THE PRESENTED STUDY REFERS TO THE POTENTIAL OF THIS INNOVATIVE RESEARCH IN THE CONTEXT OF THE REHABILITATION OF THIS POPULATION AS AN EVALUATION METHOD.
Keywords: Visually Impaired, Gait; Balance; Child; Pre-teen